2015
DOI: 10.3168/jds.2014-8820
|View full text |Cite
|
Sign up to set email alerts
|

Performance of early-lactation dairy cows as affected by dietary starch and monensin supplementation

Abstract: The objective of this study was to evaluate the effect of postpartum dietary starch content and monensin supplementation throughout the periparturient period and into early lactation on production performance of dairy cows during early lactation. Prior to parturition, primiparous (n=21) and multiparous (n=49) Holstein cows were fed a common controlled-energy close-up diet with a daily topdress of either 0 or 400mg/d monensin. From d 1 to 21 postpartum, cows were fed a high-starch (HS; 26.2% starch, 34.3% NDF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 35 publications
7
43
3
1
Order By: Relevance
“…Contrary to the results of current study, Rabelo et al (2003) and McCarthy et al (2015) reported that animal responses to high-starch diets in DMI or milk yield were greater. The discrepancy between their studies (Rabelo et al, 2003;McCarthy et al, 2015) and our study might be explained by differences in close-up diets that the animals were fed before calving, as proposed by Dann (2016); cows were fed controlled-energy closeup diets in our study to reduce postpartum metabolic complications Janovick et al, 2011), but high-starch close-up diets were fed in the previous studies (Rabelo et al, 2003;McCarthy et al, 2015). In the study of Rabelo et al (2003), even the low-energy close-up diet contained 38.2% NFC, which was much higher than that of our study (25.6% NFC).…”
Section: Effects Of Starch Content Of Fresh Dietscontrasting
confidence: 99%
“…Contrary to the results of current study, Rabelo et al (2003) and McCarthy et al (2015) reported that animal responses to high-starch diets in DMI or milk yield were greater. The discrepancy between their studies (Rabelo et al, 2003;McCarthy et al, 2015) and our study might be explained by differences in close-up diets that the animals were fed before calving, as proposed by Dann (2016); cows were fed controlled-energy closeup diets in our study to reduce postpartum metabolic complications Janovick et al, 2011), but high-starch close-up diets were fed in the previous studies (Rabelo et al, 2003;McCarthy et al, 2015). In the study of Rabelo et al (2003), even the low-energy close-up diet contained 38.2% NFC, which was much higher than that of our study (25.6% NFC).…”
Section: Effects Of Starch Content Of Fresh Dietscontrasting
confidence: 99%
“…Milk yield at the corresponding milking was used to weight milk composition and calculate yield of components. Weekly average yield of ECM were calculated from weekly yield and composition as described by McCarthy et al (2015).…”
Section: Individual Animal Sampling Analytical Methods and Calculatmentioning
confidence: 99%
“…The average of the 2 BCS were used for sta-tistical analysis. Weekly calculations of prepartum and postpartum net energy balance (EBAL) were determined according to NRC (2001) equations as described by McCarthy et al (2015).…”
Section: Individual Animal Sampling Analytical Methods and Calculatmentioning
confidence: 99%
“…Grain legumes are feedstuffs of high protein and metabolizable energy content (McCarthy et al. ). They are readily accepted by cattle, and animals require little adaptation to avoid rumen acidosis and reduced intakes.…”
Section: Introductionmentioning
confidence: 99%
“…Among dietary protein sources, research has clearly shown that legumes can increase growth rates in ruminants due to higher nitrogen utilisation efficiency and dry matter intake (Speijers et al 2004;Marley et al 2007;Chand et al 2014). Grain legumes are feedstuffs of high protein and metabolizable energy content (McCarthy et al 2015). They are readily accepted by cattle, and animals require little adaptation to avoid rumen acidosis and reduced intakes.…”
Section: Introductionmentioning
confidence: 99%